Insomnia: use of exogenous melatonina and its implications (Research, Society and Development, 2023)
This article aims to identify the main impacts of the use of exogenous melatonin as a sleep inducer in adults. The study comprised a systematic literature review based on the PubMed/MEDLINE database. The importance of sleep has been demonstrated in several ways and sleep deprivation is associated with physical and cognitive impairments. Insomnia is a sleep disorder characterized by difficulty falling or staying asleep. In this regard, many studies have sought to identify the effectiveness of the use of exogenous melatonin on sleep disorders, also evaluating the intrinsic adverse effects of this use. Very positive impacts related to the use of this exogenous melatonin were observed, as there was an increase in the total period of sleep and absence of dependence, tolerance, hangovers or even serious adverse effects. However, it is important to point out that more studies related to the subject are needed, which aim at a safer administration, considering the specificities of each person, such as age group, sex, preexisting diseases, possible drug interactions, among other aspects.